Confronting the DeFi Revolution: A Comparative Analysis of the Application of New Zealand’s Personal Property Securities Act 1999 to Cryptoassets - Mandhan, Sameer (Victoria University of Wellington Law Review, 2025)
The financial sector in the 21st century is experiencing a revolution. The major disruptor is decentralised finance (DeFi) which leverages emerging blockchain technology to eliminate the need for centralised financial institutions and empowers individuals with peer-to-peer digital exchanges. DeFi is underpinned by cryptoassets such as bitcoin, ether, and non-fungible tokens (NFTs). As DeFi offerings have become increasingly sophisticated, important legal issues have arisen. One such issue is whether the law is appropriately positioned to recognise and give effect to the use of cryptoassets as collateral in lending arrangements. The lack of legal certainty at present poses a substantial risk to market participants who are, for the most part, transacting blindly. This article, therefore, addresses the applicability and comparative suitability of New Zealand’s Personal Property Securities Act 1999 (PPSA) to cryptoasset collateral, using the recent Singaporean case of Chefpierre as a test case. It argues that the PPSA is generally better positioned than English (Singaporean) secured credit law to respond to the emerging use of cryptoassets as collateral. Nevertheless, the challenges posed by cryptoasset collateral necessitate legislative change; in particular, change to the PPSA’s perfection requirements and priority rules. After reviewing and analysing recent legal developments in the United Kingdom and the United States, this article proposes that a number of bespoke rules and concepts designed to respond to cryptoassets be introduced into the PPSA.